Pamela’s signifying signs and gestures: A semiotic analysis - Beloufa, Chahra; Kholoud, Al Ghamedi (Lililacs Journal, 2023)
In this paper, the feminine character of Pamela is explored throughout the epistolary novel. One is concerned with how Pamela’s constructed character as a female figure is represented with language and action, rather than adopting a defending position of the suppressed females in the 18th century. Pamela’s politeness and indirectness in her letters are aspects of her virtue and femininity. However, her language and use of specific politeness strategies, can also be considered a way of manipulating Mr B. Through her voice, there is be a kind of gradual unity of the female and male voices. Pamela is a representative of a doubled voice, exhibiting both of her inner and outer femininity. In this study, Pamela’s language is analysed using Julia Kirteva’s concept of semiotics. Keywords: Semiotics, Pamela, sign language, verbal language, femininity